2012
DOI: 10.5194/acp-12-6645-2012
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of water-soluble organic carbon, dicarboxylic acids, ketocarboxylic acids, and α-dicarbonyls in Central Himalayan aerosols

Abstract: Abstract. Aerosol samples were collected from a high elevation mountain site (Nainital, India; 1958 m a.s.l.) in the central Himalayas, a location that provides an isolated platform above the planetary boundary layer to better understand the composition of the remote continental troposphere. The samples were analyzed for water-soluble dicarboxylic acids (C 2 -C 12 ) and related compounds (ketocarboxylic acids and α-dicarbonyls), as well as organic carbon, elemental carbon and water soluble organic carbon. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
44
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 90 publications
12
44
5
Order By: Relevance
“…Concentrations of phthalic (Ph) acid (mean: 13 ng m −3 ), a tracer for vehicle emissions (Kawamura and Ikushima, 1993) are about 2 folds lower than that from Chennai (mean: 21 ng m −3 ) and 7 folds lower than that from Hong Kong (mean: 84 ng m −3 ). We found that concentration of tPh acid in PM 2.5 is similar to that reported from Sapporo (mean: 2.6 ng m −3 , Aggarwal and Kawamura, 2008) but is lower than those from Chennai (mean: 52 ng m −3 , Pavuruli et al, 2010) and Nainital (mean: 4.3 ng m −3 , Hegde and Kawamura, 2012). tPh could be produced from open burning of solid waste (plastic) (Simoneit et al, 2005;Kawamura and Pavuluri, 2010), which occurs commonly in Tanzania.…”
Section: Comparison Of Molecular Composition Of Diacids and Related Csupporting
confidence: 63%
See 1 more Smart Citation
“…Concentrations of phthalic (Ph) acid (mean: 13 ng m −3 ), a tracer for vehicle emissions (Kawamura and Ikushima, 1993) are about 2 folds lower than that from Chennai (mean: 21 ng m −3 ) and 7 folds lower than that from Hong Kong (mean: 84 ng m −3 ). We found that concentration of tPh acid in PM 2.5 is similar to that reported from Sapporo (mean: 2.6 ng m −3 , Aggarwal and Kawamura, 2008) but is lower than those from Chennai (mean: 52 ng m −3 , Pavuruli et al, 2010) and Nainital (mean: 4.3 ng m −3 , Hegde and Kawamura, 2012). tPh could be produced from open burning of solid waste (plastic) (Simoneit et al, 2005;Kawamura and Pavuluri, 2010), which occurs commonly in Tanzania.…”
Section: Comparison Of Molecular Composition Of Diacids and Related Csupporting
confidence: 63%
“…Based on the filed experiments, aqueous aerosol phase production of oxalic acid was reported in urban and suburban sites (Miyazaki et al, 2009;He and Kawamura, 2010). However, when compared to literature values, our C 3 /C 4 ratios are slightly lower than those (1.5) reported in Tokyo (Kawamura and Ikushima, 1993) and 1.4 in Chennai but comparable to those (0.84) in Nainital, India (Hegde and Kawamura, 2012) and those (1.3) in Jeju Island in the East China Sea .…”
Section: Comparison Of Molecular Composition Of Diacids and Related Ccontrasting
confidence: 53%
“…Glyoxylic acid (ωC 2 ) is an intermediate compound to produce oxalic acid (C 2 ) (Kawamura et al, 1996a;Warneck, 2003;Lim et al, 2005;Hegde and Kawamura, 2012;Wang et al, 2012). Thus, ωC 2 / C 2 ratios can serve as a tracer to evaluate the oxidation process of organic aerosols.…”
Section: Compositional Changes Of Dicarboxylic Acidsmentioning
confidence: 99%
“…Levoglucosan, a saccharide that is used as a tracer for biomass burning (Simoneit et al, 1999), was selected to represent category I. Succinic acid, often identified as one of the most abundant dicarboxylic acids in atmospheric aerosol samples (Rogge et al, 1993;Chebbi and Carlier, 1996;Kerminen et al, 2000;Kawamura et al, 2001a, b;Narukawa et al, 2002, Jung et al, 2010Hegde and Kawamura, 2012), was chosen to represent category II. The humic substances Nordic aquatic fulvic acid reference (NAFA) and Fluka humic acid (HA), obtained from the International Humic Substance Society (IHSS), were chosen as model compounds for category III.…”
mentioning
confidence: 99%